Perspektiv på ålder i vardagslivets interaktioner (Sociologisk Forskning, 2014)
Perspective on age in everyday interactionsThe aim of the article is to discuss how ethnomethodology and (symbolic) interactionism may contribute to sociological studies on age in everyday interactions. A theoretical framework on age, ‘age-as-accomplished’, inspired by ethnomethodology and symbolic interactionist approach has been proposed by Laz (1998; 2003). Our comparison of these approaches show, that the perspectives are incompatible, for example with regard to the definitions of culture, interaction and meaning. As such issues are not discussed by Laz, the theoretical framework is lacking in transparency and clarity. Ultimately the definition of ‘age as accomplished’ is not congruent with the notions of meaning and interpretation as used by Laz. In some respects the perspectives may though be complementary and valuable in age studies, for example the detailed study of situated norms in ethnomethodology, as well as some new developments within (symbolic) interactionist perspectives focusing on social status, and issues of subordination and superordination as relational processes.
Keywords: age studies; ’age as accomplished’; ethnomethodology; symbolic interactionism